2002
DOI: 10.1017/s0265051702000128
|View full text |Cite
|
Sign up to set email alerts
|

A study of adults' attitudes, perceptions and reflections on their singing experience in secondary school: some implications for music education

Abstract: Despite pockets of excellence, singing in British secondary schools is not only weak but in a state of continuing decline. The unpopularity of singing is well documented but the reasons for that unpopularity are less certain. Through interviewing adults between the ages of 20 and 40 about their school days, the authors located the principal sources of most people's unease with singing, and also the seat of pleasure among those who enjoyed it. Some differences between age groups and the sexes emerged through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 2 publications
2
21
1
1
Order By: Relevance
“…While the collective understanding of the value of singing continues to grow, much of the existing research has focused on teachers' perceptions of adolescent singers (Finney, 2000), or on adults reflecting back upon their experiences (Harrison, 2007 Durrant, 2002). Difficulties of motivating adolescent singers in the face of inappropriate primary school experiences, peer pressure and embarrassment were reported in Finney's (2000) study with of 40 secondary school music teachers, leaving themwho were left with a feeling of uncertainty with regards to motivating their students.…”
Section: Takedownmentioning
confidence: 99%
“…While the collective understanding of the value of singing continues to grow, much of the existing research has focused on teachers' perceptions of adolescent singers (Finney, 2000), or on adults reflecting back upon their experiences (Harrison, 2007 Durrant, 2002). Difficulties of motivating adolescent singers in the face of inappropriate primary school experiences, peer pressure and embarrassment were reported in Finney's (2000) study with of 40 secondary school music teachers, leaving themwho were left with a feeling of uncertainty with regards to motivating their students.…”
Section: Takedownmentioning
confidence: 99%
“…In fact, Hallam, Rogers, and Creech (2008) suggested that stereotyping "may be an inhibitory factor for boys, who may come under great pressure from peers if they engage in any activity that is seen as 'feminine'" (p. 15). Females are often reported as enjoying their musical participation, whereas boys cite bad experiences with a teacher as being a significant reason for why they do not enjoy the subject (Turton & Durrant, 2002). Collins (2012) described the adolescent male ecosystem as a complex and delicate balance of messages and experiences that can profoundly affect boys' attitude of being involved in musical activities.…”
Section: Introductionmentioning
confidence: 99%
“…The children's interest in singing did not seem to be related to their singing skill as measured on a singing test (Mizener 1993). In a similar study, conducted on randomly selected British adults (20-40 years), more women than men reported that they enjoyed singing at school than men (Turton and Durrant 2002). Furthermore, in Clift and Hancox's study (2001) 75% of participants agreed on emotional benefits of choral singing and Durrant (2005) concluded that Finnish men, who were not used to expressing their emotions in daily life could use choir singing as a platform for their emotional expressions.…”
Section: Personal and Emotional Aspects Of Choral Singingmentioning
confidence: 78%
“…These benefits are believed to be both immediate (Kreutz et al 2004) and long term (Bannan and Montgomery-Smith 2008). In surveys of the general population, the majority of people (61-88%) report that they enjoy singing (Chong 2010;Mizener 1993;Richards 1999;Turton and Durrant 2002).…”
Section: Personal and Emotional Aspects Of Choral Singingmentioning
confidence: 99%